Identification of a Novel Mutation of Extracellular Matrix Protein 1 Gene in a Chinese Family with Lipoid Proteinosis - Xu M; Zhou J; Yan J; Wang J (Dove Medical Press, 2023)
Mengjun Xu, Jiong Zhou, Jianliang Yan, Jianyou Wang Department of Dermatology, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of ChinaCorrespondence: Jianyou Wang, Department of Dermatology, Second Affiliated Hospital, Zhejiang University School of Medicine, 88 Jiefang Road, Hangzhou, 310009, People's Republic of China, Email 2101087@zju.edu.cnAbstract: Lipoid proteinosis (LP) is a rare autosomal recessive disorder caused by mutations in extracellular matrix protein 1 (ECM1), a glycoprotein expressed in skin. Whole-exome sequencing (WES) was used to investigate two Chinese siblings with suggestive clinical features of LP. They shared one known (c.960G>A) and one novel (c.1081G>T) pathogenic variant in ECM1 gene, inherited from their unaffected parents. The novel mutation (c.1081G>T) led to a termination codon at position 361 and caused nonsense-mediated mRNA decay and lost the function. Our finding expands the genetic etiology spectrum of LP.Keywords: lipoid proteinosis, mutation, extracellular matrix protein 1, ECM1